Expression of proteins related to thyroid hormone function in the uterus is down‐regulated at the day of implantation in hypothyroid pregnant rats. (12th March 2019) - Salleh, Naguib; Sayem, Abu Sadat Md; Giribabu, Nelli; Khaing, Si Lay
Abstract: Hypothyroidism has been linked to infertility, but the mechanisms underlying infertility‐related hypothyroidism have yet to be fully elucidated. Therefore, in this study, effects of hypothyroidism on expression of the proteins related to thyroid hormone function in the uterus, which were thought to play a role implantation, including thyroid hormone receptor (TR), thyroid stimulating hormone receptor (TSHR), retinoic acid receptor (RAR) and extracellular kinase (ERK) were identified. Pregnant female rats were rendered hypothyroid by giving methimazole (MMI), orally. Following hypothyroid induction, rats were grouped into control (non‐treated) and received subcutaneous thyroxine at 20, 40, and 80 μg/kg/day for five consecutive days. At Day 6, which is the day of implantation (GD 6), rats were sacrificed and the number of embryo implantation site in the uterus was calculated. Then, uterine horns were harvested and expression of the above proteins and their mRNAs were identified by Western blotting and real‐time PCR, respectively. In non‐treated hypothyroid pregnant rats, the number of embryo implantation sites decreased as compared to euthyroid and hypothyroid rats receiving thyroxine treatment. Similarly, expression of TRα‐1, TRβ‐1, TSHR, ERK1/2 and RAR proteins and mRNA in the uterus of non‐treated hypothyroid rats also decreased ( P < 0.05 when compared to euthyroid and thyroxine‐treated hypothyroid rats). In conclusion, downregulated expression of the thyroid hormone related proteins in the uterus at the day of implantation might result in infertility as reported in hypothyroid condition.